MEDIA EDUKASI TENTANG CUCI TANGAN - Amalia, Dania; Setiyowati, Eppy; Hidayah, Nur; Purnomo A.P, R. Adam; Wulandari, Maulidia Ajeng; M, Nur Sabila; H, Charisatin Rosidatul (Poltekkes Kemenkes Jambi, 2023)
Public knowledge regarding the importance of CTPS (Handwashing with Soap) is quite good, but the reality of practice in everyday life is still not optimal. However, since the COVID-19 pandemic, public knowledge and actions related to hand washing with soap have increased. Preventing the spread of the Covid-19 virus after the pandemic, including washing hands with soap or commonly known as CTPS (Washing Hands with Soap) with running water, is a community practice that reflects a clean and healthy lifestyle PHBS (Clean and Healthy Lifestyle) This study uses adolescent groups as the preferred research target. The main purpose of this study was to obtain an overview of the knowledge of adolescents in Wonokromo sub-district about CTPS (Handwashing with Soap) (Pickering et al., 2011). The method used in this CTPS (Handwashing with Soap) research is a descriptive quantitative method with material exposure through PPT and Posters to the intended audience. Data collection and processing techniques applied during the research were deep interview techniques. The level of knowledge of adolescents in Wonokromo sub-district can be said to be quite good towards the concept of CTPS (Handwashing with Soap). This knowledge can affect respondents' perceptions when doing HWWS in everyday life. It is known that the behavior of respondents in doing CTPS (Handwashing with Soap) can be classified at a fairly good level, although there are several obstacles that are influenced by internal and external factors (Hastuti Rufa Mongkita et al., 2021)